Impact of Thrifting Presence on Local Brands in Bandar Lampung According to Islamic Business Perspective - Rega Ardian; Vicky F Sanjaya; Yeni Susanti (International Publisher (YAPENBI), 2026)
This study aims to analyze the impact of the presence of the thrifting phenomenon on the sustainability of local brands in Bandar Lampung, using the perspective of Islamic business as an analysis framework. The method used is a Combination of Field research and literature, employing a qualitative approach, involving interviews with local brand owners such as Otsky, Kaway, Market Donkey, and The Done House. The results showed that the accelerated thrift trend following COVID-2019 led to significant asymmetric competition, resulting in a decrease in sales and profit margins for local brands as consumers switched to thrift products that offered unique models at much lower prices. From an Islamic perspective, the practice of trafficking illegal imports is considered vulnerable to violations of the principles of Shiddiq and Ghirar in transactions, as well as violating the principles of Al-'Adl due to the unfair advantage of avoiding legal fees. Therefore, the policy of banning the import of used clothing is justified by the Shari'ah through the principle of Mashlahah Mursalah to protect Hifzh al-Mal and hifzh an-Nafs. It is recommended that local brands use ethical integrity as the main competitive differentiation by strengthening Shiddiq and Amanah, and adopting a slow Fashion narrative that is oriented towards Mashlahah.